Metarepresentation and Evaluative Interaction - Higuita Martínez, Juan David; Gómez Palacio, Gérman David (Pensando Psicología, 2014)
This paper is derived from the investigative process driven approach to the context of evaluative interaction between teachers and students. Initially addressing the problem that is inserted into this interaction to argue the “misunderstandings” that there are and which are analyzed from metarepresentation; Then it discusses the concept, development and basic features that give the theoretical basis for understanding the proposal to the fi nal assessment of the evaluative interaction.
Keywords: metarepresentation; evaluative interaction; intentionality; intersubjectivity